2019
DOI: 10.3390/chemosensors7030042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Humidity on NO2-Sensing and Selectivity of Spray-CVD Grown ZnO Thin Film above 400 °C

Abstract: Thin films are being used more and more in gas sensing applications, relying on their high surface area to volume ratio. In this study, ZnO thin film was produced through a thermal aerosol spraying and chemical vapor deposition (spray-CVD) process at 500 °C using zinc acetate as a precursor. The phase identification and the morphologies of the film were investigated by XRD and SEM, respectively. Gas-sensing properties of the ZnO thin film were evaluated toward NO2, CO, and NO at a moderate temperature range (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Figure 9 a shows that when the H 2 concentration increases from 1250 to 10,000 ppm, the response time decreases from 70 (1.1 min) to 54 s (less than one minute) while the recovery time ( Figure 9 b) increases from 329 (5.48 min) to 491 s (8.18 min), respectively. This observed trend in the response time is in accordance with what has been reported in the literature [ 40 , 41 ]. This can be explained by the basic effects of surface coverage kinetics and diffusion phenomena.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 9 a shows that when the H 2 concentration increases from 1250 to 10,000 ppm, the response time decreases from 70 (1.1 min) to 54 s (less than one minute) while the recovery time ( Figure 9 b) increases from 329 (5.48 min) to 491 s (8.18 min), respectively. This observed trend in the response time is in accordance with what has been reported in the literature [ 40 , 41 ]. This can be explained by the basic effects of surface coverage kinetics and diffusion phenomena.…”
Section: Resultssupporting
confidence: 93%
“…In general, humidity has an effect on sensing performance, and this is more pronounced at room or low temperature, where water molecules can easily attach and dissociate on the material surface, reducing the active reaction sites. Our previous work, however, showed that at high temperature, the dissociation of water vapor occurs before reaching the material surface and sometimes has a positive effect on the sensing properties (e.g., increasing the selectivity) [ 40 ]. However, some examples in the literature report that adopting an orientation of TiO 2 towards the (002) plane can greatly reduce the effect of humidity on the sensing performance [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on the sensor properties of semiconductor metal oxides to NO gas in ambient humidity confirm the deterioration of the main sensor characteristics: response and recovery times, sensor signal, and sensitivity much more than toward NO 2 . Moreover, in some cases, the enhancement of sensor signal is observed [9][10][11][12][13]. These results indicate the complex nature of the interaction of target gases with semiconductor oxide materials in the presence of water vapor.…”
Section: Introductionmentioning
confidence: 78%
“…Hence, in the presence of humidity, water is in competition with the absorption of hydrogen at the MOX surface. The reduction in the gas sensing response in a wet environment is commonly known as the "poisoning effect of water on metal oxide sensors" [96,97]. Moreover, at elevated temperatures, moisture may also be responsible for a restructuring of the surfaces, modifying the density of oxygen absorption sites.…”
Section: Effect Of Humiditymentioning
confidence: 99%